Quantifying the Influence of Individual, Community, and Health System Factors on Quality of Life Among Inner-City African Americans With Type 2 Diabetes. Issue 2 (April 2021) - Campbell, Jennifer A.; Yan, Alice; Walker, Renee E.; Weinhardt, Lance; Wang, Yang; Walker, Rebekah J.; Egede, Leonard E.
Purpose: The purpose of this study is to examine the association of individual, community, and health system factors on quality of life among inner-city African Americans with type 2 diabetes. Methods: Primary data from a cross-sectional study with a community sample of 241 inner-city African Americans with type 2 diabetes were analyzed. Paper-based surveys were administered in which the SF-12 was used to capture the physical component (PCS) and mental component (MCS) of quality of life. Four regression approaches (sequential, stepwise with backward and forward selection, and all possible subsets regression) were used to examine the influence of individual, community, and health system factors on PCS and MCS after adjusting for relevant covariates using a conceptual framework. Results: In fully adjusted models, having less than a high school education and having major depression were associated with lower quality-of-life scores for MCS across all 4 regression approaches. Being employed was positively associated with better quality-of-life scores for PCS across all 4 regression approaches. PCS was higher across all 4 regression approaches for those reporting a history of trauma. At the health systems level, usual source of care was associated with better PCS across 3 regression approaches. Conclusions: These results highlight key factors that influence quality of life among inner-city African Americans with type 2 diabetes that could be targets for interventions in this population. However, additional research is needed to understand existing pathways that may be driving many of these relationships.